(untitled) (Islas, 2025)
Introduction: This article explores the relationship between landscape and cultural memory along the waterfront of the Historic Urban Center of Santiago de Cuba, focusing on Jesús Menéndez Avenue. It examines how former industrial buildings associated with rum and beer production form part of a heritage that integrates urban, natural, and symbolic elements, reflecting the region’s historical and cultural identity. Methods: Based on the methodology proposed by Espinosa Ocallaghan and Gómez Ortega (2022), the study evaluates landscape integration through an analysis of landscape units and visual perception areas. This approach makes it possible to identify visual quality, landscape visibility, and their relationship with the area’s cultural and heritage values. Results: The study identifies a mixed-use urban fabric with limited public services and three high-value landscape units affected by neglect. These units offer a framework for prioritizing key elements in future interventions that merge heritage conservation with community development. Conclusions: The waterfront of Santiago de Cuba is a cultural and historical space currently underutilized due to neglect and lack of maintenance. A sustainable model is proposed, one that engages the community in the conservation and enhancement of the waterfront as a vital resource for local identity.